Critical success factors for IS project implementation in Malaysian institutions of higher learning - Handayani, Dini; Abdullah, Rohaimi; Abdulgani, Montadzah Ambag; Ahmad Dahlan, Abdul Rahman (2010)
What do Information System (IS) project managers consider as critical success factors (CSFs) in IS project implementation? Project implementation is a complex process which requires simultaneous attention to a variety of factors - people, technology and processes. To determine whether a project is a success or a failure, one needs to know what are the important criteria of a project implementation in the eyes of the stakeholders. For this study, we are identifying the CSFs from a project manager's view. This study tries to identify which processes, people, tools and environment factors do experienced project managers regard as CSFs for IS projects implementation. Lessons learnt from these experienced project managers provide an important framework for establishing a sense of IS project implementation success, so that others can learn and take the necessary steps. This study is far from being exhaustive, but it can contribute to project managers by identifying and establishing the CSFs for IS project implementation, as there are not many studies concerning this being carried out for Malaysian Institution of Higher Learning (IHL).